Development and Validation of a New Lymph Node Ratio-Based Staging System for Ampullary Carcinoma After Curative Pancreaticoduodenectomy - Zhang, Xiaojie; Sun, Chongyuan; Li, Zefeng; Wang, Tongbo; Zhao, Lulu; Niu, Penghui; Guo, Chunguang; Chen, Yingtai; Che, Xu; Zhao, Dongbing (Frontiers in Oncology, 2022)
Background: Lymph node metastasis (LNM) is closely associated with the prognosis of ampullary carcinoma (AC). The purpose of this study is to explore the relationship between lymph node ratio (LNR) and the prognosis of patients with AC after curative pancreaticoduodenectomy and to establish a new LNR-based staging system. Methods: AC patients in Cancer Hospital, Chinese Academy of Medical Sciences between 1998 and 2020 were retrospectively reviewed as training cohort, and AC patients in SEER database between 2010 and 2018 were obtained as validation cohort. Within the training group, Kaplan-Meier survival analyses and Cox proportional hazards regression were conducted to assess the prognostic value of LNR and establish a new LNR-based staging system. Then, the new staging system was compared with 8th AJCC TNM staging system both in the training and validation cohort. Results: A total of 264 patients in the training cohort and 199 patients in the validation cohort were enrolled. Significant overall survival (OS) difference was observed between LNR-low stage and LNR-high stage in both training (P=0.001) and validation cohort (P<0.001). Then a new LNR-based staging system was developed. Under the new system, the number of patients in the training cohort and validation cohort of stage I, stage II, and stage III were 30 (11%) vs. 18 (9%), 190 (72%) vs. 96 (48%), 44 (17%) vs. 85 (43%), respectively. The new staging system better separated patients with respect to survival than the 8th AJCC TNM staging system. Conclusions: The new LNR-based staging system had better discriminability for predicting survival in AC patients after curative pancreaticoduodenectomy. More data are needed for further validation.